#### Answer

$x=-\displaystyle \frac{7}{6}$

#### Work Step by Step

$ 36x^{2}+84x+49=0\qquad$... solve with the Quadractic formula. $a=36,\ b=84,\ c=49$
$ x=\displaystyle \frac{-b\pm\sqrt{b^{2}-4ac}}{2a}\qquad$... substitute $b$ for $84,\ a$ for $36$ and $c$ for $49$.
$ x=\displaystyle \frac{-84\pm\sqrt{(84)^{2}-4\cdot(36)\cdot 49}}{2\cdot 36}\qquad$... simplify.
$x=\displaystyle \frac{-84\pm\sqrt{7056-7056}}{72}$
$x=\displaystyle \frac{-84\pm\sqrt{0}}{72}$
$x=\displaystyle \frac{-84}{72}$
$x=-\displaystyle \frac{7}{6}$